Perceptions of Economic Inequality in Colombian Daily Life: More Than Unequal Distribution of Economic Resources - García-Sánchez, Efraín; Willis, Guillermo B.; Rodríguez-Bailón, Rosa; García-Castro, Juan Diego; Palacio-Sañudo, Jorge; Polo, Jean; Rentería-Pérez, Erico (Frontiers in Psychology, 2018)
Research on perceptions of economic inequality focuses on estimations of the distribution of financial resources, such as perceived income gaps or wealth distribution. However, we argue that perceiving inequality is not limited to an economic idea but also includes other dimensions related to people’s daily life. We explored this idea by conducting an online survey (N=601) in Colombia, where participants responded to an open-ended question regarding how they perceived economic inequality. We performed a content analysis of 1,624 responses to identify relevant topics and used network analysis tools to explore how such topics were interrelated. We found that perceived economic inequality is mainly represented by identifying social classes (e.g. the elites vs. the poor), intergroup relations based on discrimination and social exclusion, public spaces (e.g. beggars on streets, spatial segregation), and some dynamics about the distribution of economic resources and the quality of work (e.g. income inequality, precarious jobs). We discuss how different perceptions of economic inequality may frame how people understand and respond to inequality.